2019
DOI: 10.1055/a-0848-8271
|View full text |Cite
|
Sign up to set email alerts
|

Sphincterotomy plus balloon dilation versus sphincterotomy alone for choledocholithiasis: a meta-analysis

Abstract: Background Endoscopic sphincterotomy plus balloon dilation (ESBD) is considered to be a promising method for the removal of large common bile duct (CBD) stones. However, when compared with endoscopic sphincterotomy (EST) alone, the efficacy and safety of ESBD remain controversial. This meta-analysis aimed to compare the efficacy and safety of ESBD vs. EST for the removal of large CBD stones. Methods Electronic databases were searched up to 15 July 2018 for literature that compared ESBD with EST for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…A total of 24 articles were used in the analysis with data abstracted from their full text. 10 , 23 45 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 articles were used in the analysis with data abstracted from their full text. 10 , 23 45 …”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have shown that endoscopic sphincterotomy plus balloon dilation was safe and effective for large CBDS removal, owing to the improvements of laser technology, more and more endoscopists preferred lithotripsy plus balloon dilation. [26][27][28] Peroral cholangioscopy-guided lithotripsy achieved a technical success rate of 80%-86% in a single procedure, and was signi cantly more likely indicated for stones ≤30 mm in size than for stones with >30 mm in size. 29,30 In the present study, no CBDS had a size of 30 mm, and the technical success rate was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Following a 2003 report on endoscopic papillary large balloon dilation (EPLBD) [4], major changes have been made to refine the technique used to remove difficult stones. The improved approach increases the success rate of initial complete stone removal, decreases the treatment duration, and reduces the need for lithotripsy [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%